(untitled) (Revista Cocar, 2018)
Objetiva-se demonstrar traços étnico-culturais identitários e aspectos educacionais indígenas dos descendentes do povo Kanindé da localidade de Fernandes, Aratuba, Ceará, Brasil. O problema norteador da pesquisa desponta da histórica tentativa eurocêntrica de apagar, ofuscar e/ou destruir o legado cultural de nossos ancestrais indígenas. Metodologicamente trata-se de um estudo empírico, descritivo-exploratório e de abordagem qualitativa. Como procedimento técnico, utiliza-se o estudo de caso etnográfico. Quanto às técnicas de geração de dados, adotam-se documentos, cadernos/notas de campo com observações diretas, entrevistas, registro de fatos, fotografias, vídeos e artefatos de uso cotidiano do povo indígena Kanindé. Como fundamento teórico-epistemológico, acolhem-se autores como Certeau (1994), Chartier (1990), Geertz (1978), Grando (2010) e Ribeiro (1983). Conclui-se que o povo Kanindé resiste, preserva e mantém viva sua identidade étnico-cultural. Palavras-chave: Povo Kanindé. Identidade étnico-cultural. Educação. Kanindé People of Aratuba-CE: history, ethnic-cultural affirmation and education Abstract It aims to demonstrate ethnic-cultural identity traits and indigenous educational aspects of the descendants of the Kanindé people from Fernandes, Aratuba, Ceará, Brazil. The guiding problem of research emerges from the historic Eurocentric attempt to erase, obfuscate, and/or destroy the cultural legacy of our native ancestors. Methodologically this is an empirical, descriptive-exploratory and qualitative approach. As a technical procedure, the ethnographic case study is used. Regarding data generation techniques, documents, notebooks/field notes with direct observations, interviews, record of facts, photographs, videos and daily use artifacts of the Kanindé indigenous people were adopted. As a theoretical-epistemological foundation of this research, authors such as Certeau (1994), Chartier (1990), Geertz (1978), Grando (2010), and Ribeiro (1983). It is concluded that the Kanindé people resist, preserve and keep alive their ethnic-cultural identity. Keywords: Kanindé people. Ethnic-cultural identity. Education.